Liberalisme dan Identitas Nasional sebagai Pulchrum Bangsa Indonesia; Terang Filsafat Keindahan Aquinas - Raimundus Awur; Armada Riyanto; Mathias Jebaru Adon (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
This paper delves into the impact of liberalism on Indonesia and national identity through a literature review and qualitative research. The author identifies the complexities of liberalism in Indonesia and its effects on the diverse societal structure. The literature review focuses on understanding national identity, exploring key aspects, and analyzing relevant literature in the context of a diverse society. Qualitative methods are used to evaluate social reality, integrating insights from the literature review into Indonesia's specific context. The primary analysis centers on the intricate relationship between liberal ideologies and national identity, navigating the dynamics of social and political spheres. Introducing Pulchrum, a mediating concept based on Thomas Aquinas's philosophy, the paper depicts a harmonious balance between liberalism and national identity. The philosophical analysis suggests that harmony between freedom and traditional values can create beauty in Indonesian society. The research yields profound insights into the complex relationship between liberalism and national identity in Indonesia, emphasizing the potential for achieving harmonious solutions. The implications of this study provide a basis for holistic thinking, balancing freedom with local and national values to foster a strong, united, and diverse society.